Arenobufagin Inhibits the Phosphatidylinositol 3-kinase/Protein Kinase B/Mammalian Target of Rapamycin Pathway and Induces Apoptosis and Autophagy in Pancreatic Cancer Cells. Issue 2 (February 2020) - Wei, Xiaolu; Yang, Jian; Mao, Yingqiu; Zhao, Haiyu; Si, Nan; Wang, Hongjie; Bian, Baolin
Abstract : Objective: The aim of the study was to investigate the effects of arenobufagin on pancreatic carcinoma in vitro and in vivo and its molecular mechanism. Methods: The proliferation of pancreatic cancer cells was detected by the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. Transmission electron microscopy was used to observe the formation of autophagic vacuoles after arenobufagin treatment. Hoechst 33258 and monodansylcadaverine fluorescence staining were performed to evaluate cell apoptosis and autophagy. Annexin V–fluorescein isothiocyanate/propidium iodide double-staining and JC-1 staining assays were used to evaluate apoptosis-related changes. Reverse-transcription polymerase chain reaction and western blotting were carried out to examine the expression of apoptosis- and autophagy-related markers after arenobufagin treatment. A tumor xenograft nude mouse model was established to evaluate arenobufagin efficacy in vivo. Results: Arenobufagin effectively inhibited the proliferation of SW1990 and BxPC3 cells and induced cell arrest, apoptosis, and autophagy. Arenobufagin upregulated the expression of apoptotic- and autophagy-related proteins while downregulated the expression of phosphatidylinositol 3-kinase family proteins. Furthermore, arenobufagin also exerted inhibitory effects on tumor growth in xenograft nude mice. Conclusions: Arenobufagin inhibits tumor growth in vivo and in vitro. The mechanism underlying arenobufagin action may involve induction of autophagy and apoptosis through the phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin pathway.